Additive effect of transcranial direct current stimulation (tDCS) in combination with multicomponent training on elderly physical function capacity: a randomized, triple blind, controlled trial - Corrêa, Fernanda Ishida; Carneiro Costa, Glaucio; Leite Souza, Paulo; Marduy, Anna; Parente, Joao; Ferreira da Cruz, Stefany; de Souza Cunha, Micaelly; Beber Freitas, Maik; Correa Alves, David; Silva, Soraia Micaela; Ferrari Corrêa, João Carlos; Fregni, Felipe (Physiotherapy theory and practice, 2023)
To evaluate the additive effect of Transcranial Direct Current Stimulation (tDCS) associated with multi-component training (MT) on the functional capacity (FC) of older adults and to assess whether these effects remain after the end of training. The secondary objectives were to evaluate the locomotion capacity, balance, functional independence, and quality of life and correlate them with functional capacity. Twenty-eight older adults were randomized into two groups: experimental (MT associated with active tDCS - a-tDCS) and control (MT associated with sham tDCS - s-tDCS). The FC was measured by the Glittre-ADL test, locomotion capacity by the 6-minute walk test, balance by the BESTest, functional independence by the FIM, and quality of life by the WHQOL. The assessments were performed pre-, post-intervention, and 30-day follow-up. There was a significant decrease in the time to the Glittre-ADL test when comparing the a-tDCS and s-tDCS groups after the interventions (139.77 ± 21.62, 205.10 ± 43.02, p < .001) and at the 30-day follow-up (142.74 ± 17.12, 219.55 ± 54.05, p < .001), respectively. There was a moderate correlation between FC and locomotion capacity and balance. The addition of tDCS potentiated the results of MT to impact FC, maintaining the positive results longer. Locomotion and balance influenced the improvement of functional capacity.